Contracting out Support Services in Future Expeditionary Operations: Learning from the Afghan Experience - Christopher Kinsey; Mark Erbel (Journal of Contemporary European Research, 2011)
As with the US led Coalition war in Iraq, the war in Afghanistan has seen an unprecedented number of private contractors being utilised in support of military operations in the country. In the case of the United States government for example, over half of its personnel in Afghanistan and Iraq are contract employees, while the same figure in the UK stands at 30 per cent and is set to increase in the coming years. This level of contractor involvement in the ‘War on Terror’ is not inconsequential. Indeed, their contribution to military operations is so large they are now able to influence NATO’s counter-insurgency operations and thus its overall strategy for fighting the Taliban and Al-Qaeda. Importantly, such involvement can be both beneficial and/or detrimental. This article first sets out to explore how NATO came to rely on so many contractors in Afghanistan and the risks this involves for the ‘War on Terror’.